DESIGNING AN INFORMATION SYSTEM INTEGRATION ENTERPRISE ARCHITECTURE WITH THE TOGAF FRAMEWORK IN THE OIL AND GAS BUSINESS UNIT CASE STUDY: PT PWS - Ervina Nisfiani, Mochammad Radja Brojas dan Widi Hastomo (Prosiding Seminar SeNTIK, 2020)
DESIGNING AN INFORMATION SYSTEM INTEGRATION ENTERPRISE ARCHITECTURE WITH THE TOGAF FRAMEWORK IN THE OIL AND GAS BUSINESS UNIT CASE STUDY: PT PWS